2020
DOI: 10.5539/gjhs.v12n13p152
|View full text |Cite
|
Sign up to set email alerts
|

The Perceptions of Professional Nurses Regarding the Performance of Cervical Cancer Screening, in Makhuduthamaga Sub-district, Sekhukhune District, Limpopo Province, South Africa

Abstract: Cervical cancer is regarded as the most common diagnosed type of cancer and resulting in high cancer related mortality amongst women. Cervical cancer related mortality rate is a serious challenge in Africa as compared to other countries, which needs a high collaborative approach amongst all health professionals. However, the higher incidence and death rate of cervical cancer implies that, high need of cervical cancer screening measures are necessary. A qualitative, descriptive approach was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Previous research in sub-Saharan Africa has revealed that barriers to cervical cancer screening exist at micro, meso, and macro levels. At the micro-level, limited provider awareness and knowledge, in uenced by cultural factors, pose challenges (14). Meso-level barriers include inadequate healthcare infrastructure (15), resource limitations, and a shortage of skilled workers (7).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research in sub-Saharan Africa has revealed that barriers to cervical cancer screening exist at micro, meso, and macro levels. At the micro-level, limited provider awareness and knowledge, in uenced by cultural factors, pose challenges (14). Meso-level barriers include inadequate healthcare infrastructure (15), resource limitations, and a shortage of skilled workers (7).…”
Section: Introductionmentioning
confidence: 99%